Musical Engagement and Parent-Child Attachment in Families With Young Children During the Covid-19 Pandemic - Steinberg, Selena; Liu, Talia; Lense, Miriam D. (Frontiers in Psychology, 2021)
The onset of the Covid-19 pandemic has disrupted the lives of families in the United States and across the world, impacting parent mental health and stress, and in turn, the parent-child relationship. Music is a common parent-child activity and has been found to positively impact relationships, but little is known about music’s role in parent-child interactions during a pandemic. The current study utilized an online questionnaire to assess the use of music in the home of young children and their parents in the USA and Canada during Covid-19 and its relationship with parents’ affective attachment with their child. Musical activity was high for both parents and children. Parents reported using music for both emotion regulation and to socially connect with their children. Parent-child musical engagement was associated with parent-child attachment, controlling for relevant parent variables including parent distress, efficacy, education and parent-child engagement in non-musical activities. These results indicate that music may be an effective tool for building and maintaining parent-child relationships during a period of uncertainty and change.